Turkish Validation and Reliability Study of the Carcinologic Handicap Index for Head and Neck Cancer Patients - Erdem Mengi; Cüneyt Orhan Kara; Anıl Yavuz (Turkish Archives of Otorhinolaryngology, 2025)
Objective: This study aimed to conduct a Turkish validation study of the Head and Neck Carcinologic Handicap Index (CHI) and investigate its effectiveness in assessing morbidity in head-and-neck tumor patients. Methods: The original CHI was translated into Turkish after a language validation study based on international standards. The study included 189 patients. Age, gender, primary tumor location, and tumor-node-metastasis stages were recorded. All patients were asked to complete the CHI form. A total of 37 patients completed the CHI form once more within 15 days to examine temporal stability. A control group was also formed to evaluate the validity of the CHI. Results: The Cronbach’s alpha coefficient was 0.898. For temporal validity, the global score showed a statistically significant correlation (p<0.001; r=0.604). There was a statistically significant difference between the global scores of the patient and the control groups (p<0.001). The global score and tumor stage differences were statistically significant (p=0.012). Review of the relationship between the tumor location and the scores showed a statistically significant difference in swallowing (p=0.001), feeding (p=0.001), and hearing (p=0.015). Conclusion: The study adapted the CHI into Turkish and showed that it can be used as a valid and reliable index for the morbidity assessment of head-neck cancer patients. We recommend frequent use of the CHI throughout follow-up.